2018
DOI: 10.1161/strokeaha.117.020474
|View full text |Cite
|
Sign up to set email alerts
|

National Practice Patterns of Obtaining Informed Consent for Stroke Thrombolysis

Abstract: Most clinicians always or often require informed consent for stroke thrombolysis. Future research should focus on standardizing content and delivery of tPA information to reduce delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
0
20
1
Order By: Relevance
“…She was informed that the stroke had affected a large vessel within the brain that governed functions such as attention, articulation, swallowing, and left-sided sensation and movement. The daughter indicated that at no point had she consented to tPA on her father's behalf (in emergency care settings, a model of presumed consent for emergency therapies, such as tPA, is common), 6 , 7 and was unclear why her father was transferred. The medical team underscored that, although tPA was one type of acute stroke therapy, EVT could also potentially remove the clot, possibly decreasing his neurologic deficits and preventing further disability.…”
Section: Case Descriptionmentioning
confidence: 99%
“…She was informed that the stroke had affected a large vessel within the brain that governed functions such as attention, articulation, swallowing, and left-sided sensation and movement. The daughter indicated that at no point had she consented to tPA on her father's behalf (in emergency care settings, a model of presumed consent for emergency therapies, such as tPA, is common), 6 , 7 and was unclear why her father was transferred. The medical team underscored that, although tPA was one type of acute stroke therapy, EVT could also potentially remove the clot, possibly decreasing his neurologic deficits and preventing further disability.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Studying an alternative to tPA involves randomizing patients to tPA vs. investigational therapy; however, the brief informed consent process for administering tPA under high level recommendation alone without the added time burden of a formal consent process for a nonstandard-of-care therapy has been reported to delay treatment. (13) In addition, patients with severe stroke symptoms may not have the capacity to consent for research, and thus require All rights reserved. No reuse allowed without permission.…”
Section: Introductionmentioning
confidence: 99%
“…Studying an alternative to tPA involves randomizing patients to tPA vs. investigational therapy; however, the brief informed consent process for administering tPA under high level recommendation alone without the added time burden of a formal consent process for a non- standard-of-care therapy has been reported to delay treatment. (13) In addition, patients with severe stroke symptoms may not have the capacity to consent for research, and thus require consent by proxy (14), which has also been shown to delay treatment, especially when consensus is needed among multiple family members. (13,15) Another source of delay could be elderly patients with cognitive impairment, a population that commonly suffers from stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite guideline recommendations that informed consent is indicated for thrombolysis, 1 there is no accepted standardized consent process for thrombolytic administration and wide variability has been reported. 2 Refusal of IV-tPA based on incorrect or incomplete understanding of its risks and benefits has the potential to affect morbidity after ischemic stroke, particularly for minority race/ethnic groups. 3 Although decisions about IV-tPA administration are usually made after consultation with a stroke fellow/attending at teaching hospitals, the process of obtaining IV-tPA consent is often assigned to neurology residents.…”
mentioning
confidence: 99%